HUBUNGAN TINGKAT PENDIDIKAN DENGAN KEMANDIRIAN LANSIA DALAM MEMENUHI KEBUTUHAN SEHARI HARI - Endang Yuswatiningsih; Hindyah Ike Suhariati (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2021)
The elderly have changes in brain structure that cause deterioration of quality of life which implies independence in carrying out daily activities. Independence is very important to care for itself in meeting basic human needs. A person's cognitive function plays an important role in memory and will mostly affect daily activities. The purpose of this study was to determine the level of education with the independence of the elderly in meeting their daily needs. This type of research is analytic with a cross-sectional approach. The population in this study were all elderly in Ngudirejo Village, Diwek District, Jombang Regency with a total sample of 35 respondents. The sampling technique is simple random sampling. The independent variable is the level of education and the dependent variable is the independence of the elderly in meeting their daily needs. Collecting data using the Barthel Index questionnaire. Processing data by editing, coding, scoring, tabulating, and analyzing using the Kruskal Wallis Test with alpha 0.05.The results showed that almost half of the respondents' education level was junior high school as much as 49% and the independence of the elderly in meeting their daily needs was mostly mild respondents as much as 63%. The results of the Kruskal Wallis Test analysis test showed that the p-value = 0.005 was smaller than the alpha value of 0.05, so H1 was accepted. The conclusion in this study is that there is a relationship between the level of education and the independence of the elderly in meeting their daily needs.